PENATALAKSANAAN FISIOTERAPI PADA KONDISI POST FRAKTUR COLLES 1/3 DISTAL DEKSTRA dengan MODALITAS INFRARED dan TERAPI LATIHAN - Fitrocha ,; Eko Budi Prasetyo (LPPM Universitas Pekalongan, 2013)
Colles' fracture is a fracture due to trauma that occurs in the wrist where the fracture is shaped like a spoon, caused by the patient fell and rested on one hand stretched in the open and pronation, and their body into the rotating arm (endorotasi). Problems on postoperative Colles' fracture is often the case, namely: pain, limitation of LGS, atrophy, decreased functional ability. To provide effective and efficient handling, then was examined for pain, limitation of LGS, muscle strength, atrophy and functional ability. In addressing these issues is given in the form Infrred modalities and exercise therapy. Having given over 6 times the action can be obtained significant results, namely: silent pain 1.5cm to be 0cm, tender 5.5cm to 2.6cm, motion pain 8.5cm to 5.4cm, LGS on elbow: R=30°-0°-15° to R=65°-0°-45°, wrist: S=30°-0°-30° to S=45°-0°-55°, F=5°-0°- 20° to F=15°-0°-25°, MCP I: S=0°-0°-30° to the S=0°-0°-55°, MCP II-V: S=0°-0°-35° to S=20°-0°-70°, MMT on the flexor-extensor elbow: 3 to 4, pronator - elbow supinator: 2 to 3, flexor - extensor wrist: 1 to 3, radial - ulnar deviator wrist: 2 to 4, MCP flexor I: 2 to 4, extensor MCP I: 3 to 4, flexor MCP II-V: 2 to 4, and extensor MCP II-V: 3 to 4, Antopometri the atrophy remains Proc. Styloideus ulna 17cm, 5cm to 19cm distal, proximal to the 13.5 cm 5cm, 17cm and 10cm proximal to, and functional ability in Duruoz Hand Index from 56 to 30. Keywords: Colles Fracture, pain, LGS, MMT, antopometri, Duruoz Hand Index.